Comparison of Cognitive Learning Outcomes and Students' Science Process Skills Between Hands on Practicum and Virtual Laboratory Based on PhET Simulation Viewed from Students' Learning Style - Cerli Anjarsari; Agus Suyatna; Viyanti (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the comparison of direct practicum with virtual laboratory practicum based on phet simulation on geometric optics material in terms of learning style, cognitive learning outcomes, and student science process skills. The research was conducted at SMA Negeri 1 Belalau, West Lampung Regency, with a population of all XI IPA class students, a sample of XI IPA 2 class of 26 students and XI IPA 3 class of 27 students taken by purposive sampling technique. This study used a research design, namely factorial design. Data analysis techniques used were N-Gain test, normality test, homogeneity test, and Two Way Anova test. The results showed that there was no significant difference after the application of hands on practicum and virtual laboratory based on PhET Simulation on optical geometry material in terms of learning style, cognitive aspect learning outcomes, and student science process skills. Based on the results of the study, it can be concluded that learning methods with hands on practicum and virtual practicum patterns are able to accommodate different learning styles of students and train learning outcomes of cognitive aspects and learning outcomes of science process skills aspects of students.